Understanding menstruation: Influence of gender and ideological factors. A study of young people's social representations. (August 2019) - Mondragon, Nahia Idoiaga; Txertudi, Maitane Belasko
This research investigates social representations of menstruation. It analyses firstly how young Spanish people understand menstruation in their everyday lives. And secondly, it explores how gender and ideological factors (liberal vs. conservative; feminist vs. non-feminist) impact on the meaning of menstruation and its implications for acceptance of this process. A free association exercise elicited by the word "menstruation" was answered by 250 people and the content was examined by lexical analysis. The results divided social representations of menstruation into two levels: firstly, a traditionalist level that is clearly linked to a negative stigmatized discourse about menstruation; and, secondly, a progressive level where two different discourses emerge, one representing liberal men and the other representing feminist women. The results show that only the feminist conception of menstruation provides an empowered and emotionally positive representation. The concept of menstruation is concluded to emerge from various sources of information, values and social conventions that are somewhat removed from its scientific meaning. The representation of menstruation is therefore understood to be situated within a social, ideological and emotional context. Accordingly, health education campaigns should frame their discourse about menstruation within a feminist perspective as their point of departure, thereby increasing their effectiveness.